Finding a place to call home: Immigration in Australia - Dockery, Michael; Duncan, Alan; Mavisakalyan, Astghik; Nguyen, Toan; Seymour, Richard (Bankwest Curtin Economics Centre, 2019)
This seventh report in the BCEC’s Focus on the States series explores the profile and evolution of immigration in Australia over recent years, and undertakes a comprehensive assessment of immigrants’ contributions to Australia’s social and economic development. The report also sheds light on the wellbeing of immigrants and their ability to take a meaningful and valued role in Australian society.